Sequência didática: a utilização de animes como estímulos para o ensino de interações elétricas - Silva, Ivan Fernando Cabral da (2024)
The current context of education in Brazil has undergone numerous political and methodological changes. The high school segment is the most affected, and any potential reforms have created increasingly profound gaps in learning. The subject of Physics, situated within the natural sciences, often finds itself sidelined due to the constant shifts in the educational system. Consequently, it becomes necessary to employ alternatives aimed at mitigating the educational deficits arising from this context. In light of this situation, this didactic sequence is premised on utilizing Ausubel’s theory of meaningful learning, incorporating elements and concepts in the creation of a podcast based on anime, with electromagnetism as the central theme of Physics. The application of this product took place in a school in Mato Grosso do Sul, involving a group of 19 students in their third year of high school. The initial step involved collecting students' prior concepts (subsumers) through a questionnaire, followed by an exploration of electromagnetism concepts. Next, students were divided into groups and encouraged to respond to questions about excerpts from anime that highlighted issues related to electromagnetism. The podcasts were developed in the final stage of the project to unify and enhance previous concepts by creating narratives and plots based on the anime. The application proved to be satisfactory given the feedback from the students, however it is not plausible to state that there was in fact significant learning, since more extensive and detailed monitoring is necessary to evaluate possible signs of significant learning, that is, it would be pertinent to continue this action to verify and compare the evolution of skills, but due to it being the last school year of these students, this analysis barrier was established.